Does energy consumption affect growth? - Saten Kumar; Don J. Webber; Antonio Paradiso (Auckland University of Technology (AUT), Faculty of Business, Economics and Law, 2012)
A review of the literature reveals discrepancies between estimates of the impact of energy consumption on output and growth. This paper highlights the importance of underlying theoretical concerns, extends a neoclassical growth model to include energy consumption, applies panel data cointegration methods that deal with cross-sectional dependence and structural breaks to a sample of thirteen high energy consuming countries, and provides empirical estimates of the impact of energy consumption on output and growth. Results suggest that energy consumption has a permanent positive effect on output levels but has no statistically significant effect on growth. We suggest that rebound effects may confound the observable effects of energy on growth and that the effects on the environment of attempts to stimulate economic growth may never be forecast correctly ex ante.
Keywords: O40; Q40; 330; Energy consumption per capita; Level effect; Growth effect